2008
DOI: 10.3858/emm.2008.40.6.629
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LPS-induced cyclooxygenase 2 and nitric oxide production by transduced PEP-1-PTEN fusion protein in Raw 264.7 macrophage cells

Abstract: Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is a tumor suppressor. Although it is well known to have various physiological roles in cancer, its inhibitory effect on inflammation remains poorly understood. In the present study, a human PTEN gene was fused with PEP-1 peptide in a bacterial expression vector to produce a genetic in-frame PEP-1-PTEN fusion protein. The expressed and purified PEP-1-PTEN fusion protein were transduced efficiently into macrophage Raw 264.7 cells in a time-and dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Our results in the present study further showed that LPS-induced cell proliferation, differentiation and collagen secretion could be inhibited in lung fibroblasts transfected with a PTEN overexpression lentivirus, which increased both PTEN levels and its dephosphorylation activity. Similar results using a PEP-1-PTEN fusion protein transfected into macrophages [ 35 ] or adenovirus-mediated PTEN gene transferred into synovial fibroblasts [ 36 ] were reported. Therefore, we reasoned that a decrease in PTEN expression and its dephosphorylation activity could be directly involved in inhibiting LPS-induced lung fibroblast cell proliferation, differentiation and collagen secretion, and overexpression of PTEN may have potential for pulmonary fibrosis treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Our results in the present study further showed that LPS-induced cell proliferation, differentiation and collagen secretion could be inhibited in lung fibroblasts transfected with a PTEN overexpression lentivirus, which increased both PTEN levels and its dephosphorylation activity. Similar results using a PEP-1-PTEN fusion protein transfected into macrophages [ 35 ] or adenovirus-mediated PTEN gene transferred into synovial fibroblasts [ 36 ] were reported. Therefore, we reasoned that a decrease in PTEN expression and its dephosphorylation activity could be directly involved in inhibiting LPS-induced lung fibroblast cell proliferation, differentiation and collagen secretion, and overexpression of PTEN may have potential for pulmonary fibrosis treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the use of endotoxin has been recently introduced as a model for the study of inflammatory pain in both animals and humans [18][19][20][21][22][23][24][25]. The administration of LPS produces a significant expression of proinflammatory mediators, like cytokines, chemokines, cyclooxygenase-2 (COX-2), and nitric oxide through activation of toll-like receptor 4 (TLR4) via modulating immune cells [26][27][28]. These inflammatory mediators play a pivotal role in the pathophysiology of many chronic pain conditions and act as a pronociceptive agent via sensitization of peripheral and central nerves [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…There is controversy concerning the role of PTEN in regulating the actions of TIR adaptors. Although macrophages from both PTEN heterozygous mice and mice specifically deficient in PTEN in myeloid cells are less responsive to TLR4 or TLR5 ligands (14,15), pharmacological inhibition of PTEN enhances TLR-mediated cytokine production (16). In addition, myeloid-specific PTEN deficiency leads to increased susceptibility to lung infection by Gram-negative and Gram-positive bacteria (17,18).…”
Section: Introductionmentioning
confidence: 99%